2022
DOI: 10.1007/s10787-022-01011-0
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and multiple sclerosis: antioxidant, anti-inflammatory and immunomodulator mechanism of action

Abstract: Background Melatonin is an indole hormone secreted primarily by the pineal gland that showing anti-oxidant, anti-inflammatory and anti-apoptotic capacity. It can play an important role in the pathophysiological mechanisms of various diseases. In this regard, different studies have shown that there is a relationship between Melatonin and Multiple Sclerosis (MS). MS is a chronic immune-mediated disease of the Central Nervous System. Aim The objective of this review was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 272 publications
(470 reference statements)
0
35
0
Order By: Relevance
“…Previous studies revealed that excessive ROS generation is associated with endoplasmic reticulum (ER) stress, which induces inflammatory response by activating the nuclear factor-kappa B (NF-κB) signaling pathway [34]. Oxidative stress is involved in the activation of NLRP3 inflammatory corpuscles, which is an important component of innate immunity involved in the process of inflammatory diseases of the CNS [35][36][37]. Latest studies have shown that NLRP3 is up-regulated in both neuropathic and inflammatory pain models, the activation of which, is also involved in the occurrence and maintenance of postoperative pain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that excessive ROS generation is associated with endoplasmic reticulum (ER) stress, which induces inflammatory response by activating the nuclear factor-kappa B (NF-κB) signaling pathway [34]. Oxidative stress is involved in the activation of NLRP3 inflammatory corpuscles, which is an important component of innate immunity involved in the process of inflammatory diseases of the CNS [35][36][37]. Latest studies have shown that NLRP3 is up-regulated in both neuropathic and inflammatory pain models, the activation of which, is also involved in the occurrence and maintenance of postoperative pain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Promising, emerging research indicates that melatonin supplementation may have therapeutic benefits for autoimmune conditions, such as multiple sclerosis (MS) and perhaps Hashimoto’s thyroiditis, most likely due to its involvement in anti-inflammatory mechanisms, oxidative stress reduction, and modulation of the gut microbiota [ 165 ]. Melatonin is linked to the seasonal relapse rate in patients with MS [ 166 ].…”
Section: Clinical Usesmentioning
confidence: 99%
“…Glutathione is one of the major antioxidant systems in the body and is susceptible to changes in redox status and nutrient supply [ 315 ]. Various research studies have confirmed that there are individual associations between melatonin and glutathione [ 165 ], and glutathione and vitamin D [ 316 ]. Thus, while not yet extensively researched, there could be an interrelationship between the collective antioxidant activities of glutathione, vitamin D, and melatonin.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…Melatonin 10.3389/fncel.2023 synthesis undergoes changes with age and in experimental demyelination (Hardeland, 2012;Wurtman, 2017). In contrast, the exogenous melatonin exhibits neuroprotective effects in animals of different age with experimental models of nervous system pathology (Hardeland, 2012;Murioz-Jurado et al, 2022). The aim of study was:(1) to evaluate changes of the brain macrophages, astrocytes, T-cells, neural stem cells, neurons and CNS functioning in the neurotoxin cuprizone-treated mice of different age; and (2) to assess in such mice the effects of exogenous melatonin and possible courses of its action.…”
Section: Introductionmentioning
confidence: 99%